Metal ion-assisted self-assembly of complexes for controlled and sustained release of minocycline for biomedical applications. (20th January 2015) - Zhang, Zhiling; Wang, Zhicheng; Nong, Jia; Nix, Camilla A; Ji, Hai-Feng; Zhong, Yinghui
Abstract: This study reports the development of novel drug delivery complexes self-assembled by divalent metal ion-assisted coacervation for controlled and sustained release of a hydrophilic small drug molecule minocycline hydrochloride (MH). MH is a multifaceted agent that has demonstrated therapeutic effects in infection, inflammation, tumor, as well as cardiovascular, renal, and neurological disorders due to its anti-microbial, anti-inflammatory, and cytoprotective properties. However, the inability to translate the high doses used in experimental animals to tolerable doses in human patients limits its clinical application. Localized delivery can potentially expose the diseased tissue to high concentrations of MH that systemic delivery cannot achieve, while minimizing the side effects from systemic exposure. The strong metal ion binding-assisted interaction enabled high drug entrapment and loading efficiency, and stable long term release for more than 71 d. Released MH demonstrated potent anti-biofilm, anti-inflammatory, and neuroprotective activities. Furthermore, MH release from the complexes is pH-sensitive as the chelation between minocycline and metal ions decreases with pH, allowing 'smart' drug release in response to the severity of pathology-induced tissue acidosis. This novel metal ion binding-mediated drug delivery mechanism can potentially be applied to other drugs that have high binding affinity for metal ions and may lead to the development of new delivery systems for a variety of drugs.